Capacity Strategies a Comparative Perspective in Manufacturing vs Service Industries - Edwina Fabiola Rayo; Ayu Christa Pratiwi Inaray; Benny Lule (SAFE-Network, 2023)
The main aim of this research is to provide a deeper understanding of how wise capacity planning can become a key success factor across various industrial sectors. It can have a positive impact on organizations by achieving optimal operational efficiency and delivering services or products that satisfy consumers. This study employs a qualitative approach focusing on literature review to explore and comprehend capacity strategies in a comparative context between manufacturing and service industries. Capacity planning holds significant importance for the expansion of all companies, particularly those operating in industrial sectors. Businesses can leverage these strategies to meet client needs, save on operational costs, and facilitate sustainable expansion. It’s crucial for companies to comprehend and address current obstacles. Key factors include accurate demand forecasting, effective company constrain management, and the ability to adapt and respond to market fluctuations. In today’s era of digitalization, companies have opportunities to employ sophisticated technologies like ERP, big data analytics, and machine learning to effectively achieve their capacity planning goals. Implementing these tools can result in more accurate forecasting and enable faster adaptation to market fluctuations. To enhance operational efficiency and align output with business objectives, companies need to engage in effective planning.